The Islamic spectrum of Malay traditional architecture: case study of Tok Abu Bakar Alang Ketak House - Abd Rashid, Mohd Sabrizaa; Abdul Halim Choo, Iryani (2025)
The Malay traditional architecture philosophy is derived from at least three main domains; Islamic religion, Malay culture practice and beliefs comprise of the do’s and the don'ts in Adat, Petua and Pantang Larang and lastly the understanding and adaptation of environmental factors. This paper objective is to highlights the parallelism between the teaching and practice of Islam, by discussing the concept and idea of the architectural design found in the Malay traditional architecture. The house of Tok Abu Bakar Alang Ketak as one of the best samples of Perak Malay Traditional house was selected as a case study. Site observation, spatial organizations analysis and cultural study were carried out to achieve the research objectives. Four scenarios of Islamic spectrum, were found to express the situations of parallelism between the practice of Islam, the Malay culture and the spatial organization of the Malay traditional architecture.